TRANSFER PRICING DECISIONS: THE ROLE OF AUDIT TENURE, TAX MINIMIZATION, AND DEBT COVENANTS - Mohamad Zulman Hakim; Siti Aisyah Ritonga; Wiwid Sukma Dewi; Elsa Dwi Leonita; Hijrah Fitrah Arrahmah (PT. ZILLZELL MEDIA PRIMA, 2026)
Transfer pricing is a common practice among multinational companies in allocating profits across related entities, which may influence tax burdens and the quality of financial reporting. This study aims to analyze the effects of audit tenure, tax minimization, and debt covenant on transfer pricing practices in basic materials sector companies listed on the Indonesia Stock Exchange (IDX). The research employs a quantitative approach using secondary data obtained from financial statements and annual reports for the period 2020–2024. The sample consists of 11 companies selected through purposive sampling, and the data are analyzed using panel data regression with the assistance of EViews 12 software. The results indicate that tax minimization, proxied by the Effective Tax Rate (ETR), has a positive effect on transfer pricing, suggesting that companies tend to engage in related-party transactions to reduce tax burdens. In addition, the debt covenant variable, measured by the Debt to Equity Ratio (DER), also shows a positive influence on transfer pricing practices, indicating that firms with higher leverage are more likely to use transfer pricing strategies to manage financial and contractual pressures. Meanwhile, audit tenure does not have a significant effect on transfer pricing practices. These findings provide empirical evidence that tax-related incentives and financial structure considerations play an important role in shaping transfer pricing behavior in the basic materials sector, and they offer valuable insights for regulators, academics, and practitioners in strengthening oversight and improving corporate governance related to transfer pricing practices.